The sounds and tastes of colours : hue and saturation in Isluga textiles - Penelope Dransart (Nuevo mundo - Mundos Nuevos, 2016)
With an emphasis on the concept of hue, this article examines colour qualities in ethnographic textiles from Isluga, in northern Chile, according to ideas concerning synaesthesia and chromaticism. It explores correspondences between light, colours, sound and taste against a historical trajectory in which industrially manufactured yarns bought in the marketplace replaced the dyeing of threads at the homestead. Attention is drawn to notions of saturation and how weavers exploit contrasts of hue, using extensive amounts of naturally coloured camelid fleece and narrow stripes of dyed colours. During much of the twentieth century, Isluga weavers restricted their use of intense colours compared to those used by weavers in other parts of the Andes. This article addresses anthropological theories of colour in the light of weavers’ metaphysical appreciation of the concept of colour saturation as their willingness to incorporate more extensive amounts of bright colours changed. It is based on the author’s fieldwork in Isluga conducted since the mid-1980s.